THE FACTORS OF AFFECTING COMMUNICATION ABILITY DURING THE ENGLISH TEACHING LEARNING PROCESS AT THE EIGHT GRADE OF SMP NEGERI 2 SESEAN - Agus Sumule (Teaching English as a Foreign Language Overseas Journal, 2016)
The objective of the study is to find out the factors affect communicationduring the teaching learning English process at the eight grade at SMP Negeri 2Sesean.In order to achieve the objectives of this study, the writer used the technique ofrandom sampling. The writer used descriptive qualitative research method, the writerconducted interviews with students and teacher and classroom observation to describethe cause of the lack of communication during the English teaching and learning ateight Grade of SMP Negeri 2 Sesean. Instruments were used to gain data were semistructure interview and then analyzed quantitatively. The population in this study werethe eight grade of SMP Negeri 2 Sesean, which consists of 95 students academic year2015/2016. Since the population of the research is too beg therefore the writer took 25students as a sample in randomly.The results indicate that students are lazy to practice English so students do sayanything when the teaching learning proces. The lack of mastery of the material. Therelationship between teachers and students, a good relationship makes the learningprocess should be very well, the lack of confidence in learning English, confidence isvery supportive of student learning and never asked so that the learning process is noteffective.